Dampak Penggunaan Qris, Persepsi Kemudahan Dan Risiko Keamanan Dengan Variabel Mediasi User Experience Terhadap Keputusan Pembelian Makanan Di Resto Tom Sushi - Calya Dini Daniswara; Vincent Didiek Wiet Aryanto; Ana Kadarningsih; Diana Aqmala (LPPM Politeknik Pratama, 2025)
This study aims to analyze the impact of the use of Quick Response Code Indonesian Standard (QRIS), perceived ease of use, and security risk on food purchasing decisions at Resto Tom Sushi, with user experience as a mediating variable. The increasing adoption of digital payments through QRIS and mobile banking (m-banking) has changed consumer transaction patterns, especially in the restaurant industry. This study uses a quantitative approach with a survey method involving QRIS and m-banking users at Resto Tom Sushi. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that the use of QRIS, perceived ease of use, and security risk had a significant effect on purchasing decisions. In addition, user experience plays a mediating role that strengthens the relationship between independent variables and purchasing decisions. These findings emphasize the importance of good user experience and digital literacy in increasing the effectiveness of digital payments and encouraging the adoption of non-cash payments in the culinary sector.